1995
DOI: 10.1074/jbc.270.21.12584
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Vitamin C (Ascorbate) and Its Oxidized Metabolite Dehydroascorbic Acid Occurs by Separate Mechanisms

Abstract: It is unknown whether ascorbate alone (vitamin C), its oxidized metabolite dehydroascorbic acid alone, or both species are transported into human cells. This problem was addressed using specific assays for each compound, freshly synthesized pure dehydroascorbic acid, the specially synthesized analog 6-chloroascorbate, and a new assay for 6-chloroascorbate. Ascorbate and dehydroascorbic acid were transported and accumulated distinctly; neither competed with the other. Ascorbate was accumulated as ascorbate by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
0
7

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(171 citation statements)
references
References 35 publications
8
155
0
7
Order By: Relevance
“…We first examined whether HepG2 cells accumulated and reduced DHA and whether part of the resulting AH was subsequently released into the extracellular space. As shown previously for other cell types (see, for example, [13,[22][23][24]), incubation of adherent HepG2 cells in itro with 80 µM DHA at 37 mC resulted in detectable intracellular AH. The concentration of AH increased time-dependently to 5 nmol\10' cells over 1 h, concurrently with a decrease in the concentration of DHA in the extracellular medium ( Figure 1A).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…We first examined whether HepG2 cells accumulated and reduced DHA and whether part of the resulting AH was subsequently released into the extracellular space. As shown previously for other cell types (see, for example, [13,[22][23][24]), incubation of adherent HepG2 cells in itro with 80 µM DHA at 37 mC resulted in detectable intracellular AH. The concentration of AH increased time-dependently to 5 nmol\10' cells over 1 h, concurrently with a decrease in the concentration of DHA in the extracellular medium ( Figure 1A).…”
Section: Resultssupporting
confidence: 76%
“…Previous studies on the uptake of extracellular DHA and its subsequent intracellular conversion to AH have commonly used erythrocytes [13,[22][23][24]. It has been suggested that erythrocytes release AH [22] ; however, the detection of AH efflux from erythrocytes resuspended at 37 mC in HBSS was hampered by haemoglobin leakage (results not shown), as this gives rise to inadvertent oxidation of AH during sample preparation [25].…”
Section: Resultsmentioning
confidence: 99%
“…At concentrations higher than ≈400 μM, relative uptake decreased. These results are consistent with the known active accumulation of ascorbate by cells to concentrations many times more than in the extracellular space [18,65,66]. The ascorbate levels in human neutrophils and monocytes in vivo [16] are similar to the levels of ascorbate taken up by HL-60 and U937 cells, using our approach.…”
Section: Cellular Uptake Of Asch − Is Higher In U937 Cells Compared Tsupporting
confidence: 89%
“…It's concentration in the blood of normal individuals varies from 5 to 90 μM [17]. However, it is actively accumulated in human tissues to a concentration as much as 50-fold greater than plasma [18]. In vitro cancer cells also accumulate ascorbate [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin E was determined at 290 nm. The lymphocyte and neutrophil number obtained from a known blood volume, together with previous data on neutrophil (30.10 À8 ml/neutrophil; Welch et al, 1995) and lymphocyte volume (21.10 À6 ml/lymphocyte; Segel et al, 1981) were used to calculate vitamin E concentration (mM) in lymphocytes and neutrophils. Vitamin E/cholesterol (mmol/mmol) ratio was also calculated.…”
Section: Vitamin E Determinationmentioning
confidence: 99%